METHODOLOGY FOR DEVELOPING GOALKEEPER TECHNIQUE IN HANDBALL - Khayitov , B.N. (Mental Enlightenment Scientific-Methodological Journal, 2025)
This article presents information on the methodology of using a complex of exercises that develop the game technique of goalkeepers in handball, as well as an analysis of its effectiveness.